CRISPR-Cas9 In Situ engineering of subtilisin E in Bacillus subtilis. - Marcus A Price; Rita Cruz; Scott Baxter; Franck Escalettes; Susan J Rosser (PLoS ONE, 2019)
CRISPR-Cas systems have become widely used across all fields of biology as a genome engineering tool. With its recent demonstration in the Gram positive industrial workhorse Bacillus subtilis, this tool has become an attractive option for rapid, markerless strain engineering of industrial production hosts. Previously described strategies for CRISPR-Cas9 genome editing in B. subtilis have involved chromosomal integrations of Cas9 and single guide RNA expression cassettes, or construction of large plasmids for simultaneous transformation of both single guide RNA and donor DNA. Here we use a flexible, co-transformation approach where the single guide RNA is inserted in a plasmid for Cas9 co-expression, and the donor DNA is supplied as a linear PCR product observing an editing efficiency of 76%. This allowed multiple, rapid rounds of in situ editing of the subtilisin E gene to incorporate a salt bridge triad present in the Bacillus clausii thermotolerant homolog, M-protease. A novel subtilisin E variant was obtained with increased thermotolerance and activity.